The CRESST dark matter search - Jochum J.; Bravin M.; Bucci C.; Bruckmayer M.; Cooper S.; Giordano S.; Feilitzsch F. von; Keeling R.; Kraus H.; Loidl M.; Lush J.; Marchese J.; et al. (2000, 2000)
Title screen